Adopsi Aplikasi Berbasis Android - Dyah Sugandini; Aprilivianto Aprilivianto; Bela Yudha Darasta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat UPN Veteran Yogyakarta, 2020)
This study aims to analyze the relative advantages, ease and visibility of the adoption of Android-based applications. The sample of this research is consumers who have used Android-based applications with a total of 100 respondents. Data were analyzed using descriptive statistics with the SPSS program. The results of this study indicate that the relative advantage, ease and visibility of the adoption of Android-based applications. Shows a high average answer. So it can be concluded that the relative advantages, ease and visibility of the adoption of Android-based applications can be used for further research related to the adoption of Android-based applications.